INTRODUCTION METHODOLOGY OF FINTECH INTO DEVELOPMENT BANKS ON THE EXAMPLE OF VNESHECONOMBANK OF RUSSIA - S. Matveevskii (Вестник университета)
The methodology for introducing financial technologies (fintech) into development banks has been considered. The methodology is based on the analysis of the characteristics of financial technologies, basic operations, the project cycle of the development bank. After the introduction of fintech, the development bank has the opportunity to solve fundamentally new tasks, which is associated with innovative ways of receiving, processing and using information. The methodology has been specified on the example of the blockchain technology in the form of a sequence of stages on the example of a typical project of Vnesheconombank of Russia. The presented methodology can be used by Vnesheconombank for planning the introduction of financial technologies.